2022
DOI: 10.1038/s41598-022-26780-0
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and characteristics of antibiotic prescription for acute COVID-19 patients in Japan

Abstract: COVID-19 is a viral infection and does not require antibiotics. The study aimed to elucidate a prescribing pattern of antibiotics for COVID-19. A nationwide cross-sectional study was conducted in Japan. The Diagnosis and Procedure Combinations (DPC) data was used to collect information, covering 25% of all acute care hospitals in the country. In 140,439 COVID-19 patients, 18,550 (13.21%) patients received antibiotics. Antibiotics were prescribed more often in inpatients (10,809 out of 66,912, 16.15%) than outp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 31 publications
(47 reference statements)
0
3
1
1
Order By: Relevance
“…According to our study findings, 94.4% of patients received antibiotics irrespective of disease severity, and 90.6% of patients received at least one antibiotic despite presenting with non-severe disease manifestations, which is a higher percentage than that previously reported (78%) in non-COVID patients [ 18 ]. However, the rate of antibiotic use in our study was lower than that observed in a study conducted in another center in Dhaka (100%) [ 6 ], but higher than those reported in other Asian countries such as Pakistan (89.7%) and Japan (13.21%) [ 19 , 20 ]. Global surveys conducted worldwide have concluded that increased use of antibiotics has been reported in more than half of the countries, with higher prevalence in LMICs [ 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 87%
“…According to our study findings, 94.4% of patients received antibiotics irrespective of disease severity, and 90.6% of patients received at least one antibiotic despite presenting with non-severe disease manifestations, which is a higher percentage than that previously reported (78%) in non-COVID patients [ 18 ]. However, the rate of antibiotic use in our study was lower than that observed in a study conducted in another center in Dhaka (100%) [ 6 ], but higher than those reported in other Asian countries such as Pakistan (89.7%) and Japan (13.21%) [ 19 , 20 ]. Global surveys conducted worldwide have concluded that increased use of antibiotics has been reported in more than half of the countries, with higher prevalence in LMICs [ 21 , 22 ].…”
Section: Discussioncontrasting
confidence: 87%
“…The same study reported that the antibiotics were prescribed to 16.15% hospitalized COVID-19 patients with lifethreatening and only 10.53%.for outpatients. 9 A study conducted in Hong Kong, only 29.1% of cases were treated with antibiotics, although only 1.84% of them had confirmed bacterial infection, in which the most frequently prescribed antibiotics were amoxicillin + clavulanic acid, ceftriaxone, and doxycycline. 16 A study conducted in Malaysia showed that the use of antibiotics was 17.1% of cases, with two or more antibiotics being given in 5.5% of cases, with the most frequently given antibiotics were amoxicillin/clavulanic acid (37.8%), followed by ceftriaxone (12.3%), piperacillin/tazobactam (13.3%), azithromycin (8.3%), and meropenem (7.0%).…”
Section: Discussionmentioning
confidence: 99%
“…5 A retrospective study reported that cephalosporins, macrolides, quinolones, and ampicillin/clavulanic acid were the most prescribed antibiotics among hospitalized COVID-19 patients. [6][7][8][9][10] A study showed the pattern of antibiotic use in patients with COVID-19 and bacterial infections, highlighting the urgent need for further research to assess the effect of COVID-19 on antimicrobial resistance at both the patient and population levels. 10 Thus, we conducted a study aimed to describe the prevalence of antibiotic use in hospitalized COVID-19 patients in hospitalized patients in secondary healthcare hospitals in Kosovo.…”
Section: Introductionmentioning
confidence: 99%
“…studies reported an overuse of antibiotics amongst COVID-19 hospitalized patients. There might be a false belief of antibiotic use as medical prophylaxis to reduce secondary bacterial infections [36][37][38][39]. These highlight the need to improve clinician adherence to the well-developed evidence-based antibiotic guidelines [38,39].…”
Section: Plos Onementioning
confidence: 99%